2017
DOI: 10.1016/j.cct.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Applying self-determination theory to the blood donation context: The blood donor competence, autonomy, and relatedness enhancement (Blood Donor CARE) trial

Abstract: The Blood Donor Competency, Autonomy, and Relatedness Enhancement (Blood Donor CARE) project was designed as a practical application of self-determination theory to encourage retention of first-time donors. Self-determination theory proposes that people are more likely to persist with behaviors that are internally-motivated, and that externally-motivated behavior can evolve and become internalized given the appropriate socio-environmental conditions. According to self-determination theory, motivation to engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…In fact, the TAM is the most widely used theoretical approach to study the usage intention of technology, although it is limited when the acceptance and use of ICT are also geared towards fulfilling emotional needs [44]. In this context, based on previous SDT research [58,69,73,74], the proposed model includes the most relevant motivational factors of this theory, and several interesting findings emerged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the TAM is the most widely used theoretical approach to study the usage intention of technology, although it is limited when the acceptance and use of ICT are also geared towards fulfilling emotional needs [44]. In this context, based on previous SDT research [58,69,73,74], the proposed model includes the most relevant motivational factors of this theory, and several interesting findings emerged.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered one of the leading motivational theories today [57]. SDT has been used to tackle motivational studies across many disciplines, including: healthcare [58], writing [59], human resources [60,61], education [62][63][64], organizations [65][66][67], and sport [68], among others.…”
Section: Self-determination Theory (Sdt)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, as described in our prior report, in addition to showing significantly greater increases in motivational autonomy, individuals in the motivational interview group also had significantly larger increases in affective attitude, self‐efficacy, and intention compared with the control group. Additional studies are needed to examine how these different psychological constructs may interact to help motivate repeat donation behavior, and we hope to address this important issue with data from a large ongoing clinical trial …”
Section: Discussionmentioning
confidence: 99%
“…Existing research on human behavior found the second type to be far more effective in motivating individuals to act in a particular way [30]. Accordingly, individuals engage in a range of behaviors, for which there is no extrinsic motivation, such as sharing knowledge [31] or donating blood [32]. A myopic focus on extrinsic motivational interventions, when it comes to encouraging security behaviors, might well be neglecting far more effective interventions [33].…”
Section: Related and Background Researchmentioning
confidence: 99%